357 SCREENING FOR CHRONIC KIDNEY DISEASE IN HUMAN IMMUNODEFICIENCY VIRUS: THE RENAL CLINIC PERSPECTIVE. Issue 1 (1st January 2007) - Hall, J.; Fulop, T.; Mena, L.; Henderson, H.; Schmidt, D.
Abstract : Purpose: In June of 2005, the Infectious Disease Society of America released guidelines recommending that all patients with human immunodeficiency virus (HIV) be screened for chronic kidney disease (CKD) with serum creatinine and urinalysis for protein. In 10/05 we began a screening program for CKD in an infectious disease clinic that cares for approximately 1, 400 patients with HIV. As an adjunct to the screening program, we founded a "CKD in HIV" clinic to handle the associated consultations. In this abstract, we present our experience during the first year of the program. Methods: Data were obtained through review of clinic and hospital records. We documented patient demographics, general health data, HIV-specific data, renal-specific data, and short-term management plans, as well as outcome for each patient referred to our clinic. Results: Thirty-six patients were referred to the CKD in HIV clinic during 10/2005-9/2006. Nineteen of 36 referrals were detected by the screening program. The reason for referral was variable. Nine of 36 (25%) were referred for nephrotic range proteinuria, and 12 of 36 (33%) were referred for non-nephrotic range proteinuria. Ten of 36(28%) had reduced GFR without proteinuria. Seven of 36 (19%) of referrals never fulfilled their clinic appointment. Of the patients seen in clinic, the mean age was 44 (± 10). Ninety-three percent were African American and 79% were male. Sixty-five percent had undetectable viral loads and 69% had CD4 > 200 at the time of their clinic evaluation. Seventy-nine percent were on antiretroviral therapy (ART). The mean urine protein/creatinine ratio for patients with proteinuria was 3.49 ± 5.3. Nine patients underwent renal biopsy: three had HIV-associated nephropathy (HIVAN), three had non-HIVAN focal segmental glomerulosclerosis, two had immune complex disease, and one had diabetic nephropathy. Management changes following CKD consultation were frequent, including initiation of renin-angiotensin system blockade and modification or initiation of ART, and in two cases, steroids were initiated. Conclusion: In a brief period of time, a number of referrals have been made to the CKD in HIV clinic. Pathology was varied, and management changes were frequent. We feel that a dedicated CKD/HIV clinic has a role in the management of HIV patients.